2020
DOI: 10.1523/jneurosci.1767-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Entraining Stepping Movements of Parkinson's Patients to Alternating Subthalamic Nucleus Deep Brain Stimulation

Abstract: Patients with advanced Parkinson's can be treated by deep brain stimulation of the subthalamic nucleus (STN). This affords a unique opportunity to record from this nucleus and stimulate it in a controlled manner. Previous work has shown that activity in the STN is modulated in a rhythmic pattern when Parkinson's patients perform stepping movements, raising the question whether the STN is involved in the dynamic control of stepping. To answer this question, we tested whether an alternating stimulation pattern r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…However, several small studies have found that low-frequency stimulation (<100 Hz) can improve gait in PD (Moreau et al, 2008 ; Xie et al, 2016 ). Additionally, physiology studies have shown a dynamic temporal relationship between intrinsic basal ganglia oscillations and the various components of gait (Fischer et al, 2018 , 2020 ). Novel stimulation paradigms have been proposed as a possible alternatives to conventional DBS that may improve the suboptimal responses to classic DBS approaches (Akbar et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, several small studies have found that low-frequency stimulation (<100 Hz) can improve gait in PD (Moreau et al, 2008 ; Xie et al, 2016 ). Additionally, physiology studies have shown a dynamic temporal relationship between intrinsic basal ganglia oscillations and the various components of gait (Fischer et al, 2018 , 2020 ). Novel stimulation paradigms have been proposed as a possible alternatives to conventional DBS that may improve the suboptimal responses to classic DBS approaches (Akbar et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an alternating DBS pattern, consisting of rhythmic intermittent reductions in stimulation intensity with a fixed offset between the right and left STN, was shown to significantly manipulate step timing. 16 These results have raised the possibility that alternating stimulation in the STN may be a promising DBS pattern for gait control in PD. In this study, we showed that alpha and beta oscillations in the PPN were modulated relative to the gait phase of the contralateral foot in both patients with MSA and PD.…”
Section: Potential Implications In Ppn Dbsmentioning
confidence: 99%
“…Considering the rhythmic structure of movements during gait, conventional continuous DBS may be suboptimal for improving gait control. 16 Understanding how neural activity in the PPN is modulated during gait could be a crucial step in improving the therapeutic effects of PPN DBS. Increased alpha power in the PPN has been observed in human patients during locomotion including free walking or imaginary gait, 3,17,18 and increased alpha power in the PPN during walking correlated with gait performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several small studies have found that low-frequency stimulation (<100 Hz) can improve gait in PD (Moreau et al, 2008;Xie et al, 2016). Additionally, physiology studies have shown a dynamic temporal relationship between intrinsic basal ganglia oscillations and the various components of gait (Fischer et al, 2018(Fischer et al, , 2020. Novel stimulation paradigms have been proposed as a possible alternatives to conventional DBS that may improve the suboptimal responses to classic DBS approaches (Akbar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%